6 x - 6 - 10 x + 6 = - 4 x
2007-11-15 04:56:30
·
answer #1
·
answered by Como 7
·
1⤊
0⤋
this is plenty easier than it first seems, somewhat some human beings get caught out. As the two brackets are quadratic equations you do no longer could desire to do any factorising. you initiate with (5x^2 + 3x +4) - (2x^2 - 6x + 3) in basic terms do away with the brackets to make it easier: 5x^2 + 3x +4 - 2x^2 + 6x - 3 From right here it could actually be trouble-free 5x^2 - 2x^2 , 3x + 6x and four - 3 So the respond is 3x^2 + 9x +a million Making B = 9 wish this enables
2016-11-11 03:58:23
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
2*3x = 6x then 2*-3= -6 = 6x-6 hold on to that
-2*5x = -10x then -2*-3= 6 -10x +6
put the like terms together 6x-10x -6+6 = -4x
2007-11-11 07:12:33
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
2(3x - 3) - 2(5x - 3) =
(6x - 6) - (10x - 6) =
6x - 6 - 10x + 6 =
6x - 10x - 6 + 6 =
- 4x
2007-11-11 07:10:54
·
answer #4
·
answered by Michelle H 1
·
0⤊
0⤋
First distribute the coefficients (the two's).
(6x-6)+(6x+6)
6x - 6 - 10x + 6
-4x
2007-11-11 07:08:53
·
answer #5
·
answered by npontello12 2
·
0⤊
0⤋
= 6x-6-10x+6
= -4x
2007-11-11 07:11:49
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
2(3x-3)-2(5x-3) =
(6x-6)-(10x+6) = -4x
2007-11-11 07:08:43
·
answer #7
·
answered by vanle24 1
·
1⤊
0⤋
6x-6-10x-6
=-4x-12
2007-11-11 07:09:19
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
6x-6-10x-6
4x/4=12/4
x=3
2007-11-11 07:16:46
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋
you use distribute property
6x-6-10x-6
you combine like terms
-4x-12
2007-11-11 07:07:41
·
answer #10
·
answered by Gee Kai 4
·
0⤊
0⤋